#IAMHUSSEINI: television and mourning during the COVID-19 pandemic. Issue 2 (3rd April 2022) - Sparey, Rhys Thomas
ABSTRACT: This article is a study of mourning among Shi'a Muslims during the COVID-19 pandemic through a call-in talk show called #IAMHUSSEINI . By analyzing the discourses of callers and presenters and locating them within a visual context of the television studio, this article shows how the viewership of #IAMHUSSEINI constitutes a televisual majlis (Arabic: 'assembly') composed of more than passive asynchronous consumption and resembling what Patrick Eisenlohr refers to as 'atmospheres'. This article argues that the COVID-19 pandemic drove #IAMHUSSEINI to recalibrate to expectations of a spatially proximate ritual, rather than sustaining a 'natively digital' aesthetic, repurposing Richard Rogers' approach to digital methods. This change brought about a tacit understanding of the televisual majlis among #IAMHUSSEINI's viewers. This article therefore posits a difference between 'spatial intercorporeality', in which bodies are mediated by spatial proximity, and 'functional intercorporeality', in which they are mediated by the material preconditions of a shared activity.